Magnetic Nanomaterials Mediate Electromagnetic Stimulations of Nerves for Applications in Stem Cell and Cancer Treatments - Lei Wang; Yefan Duan; Shujie Lu; Jianfei Sun (Journal of Functional Biomaterials, 2023)
Although some progress has been made in the treatment of cancer, challenges remain. In recent years, advancements in nanotechnology and stem cell therapy have provided new approaches for use in regenerative medicine and cancer treatment. Among them, magnetic nanomaterials have attracted widespread attention in the field of regenerative medicine and cancer; this is because they have high levels of safety and low levels of invasibility, promote stem cell differentiation, and affect biological nerve signals. In contrast to pure magnetic stimulation, magnetic nanomaterials can act as amplifiers of an applied electromagnetic field in vivo, and by generating different effects (thermal, electrical, magnetic, mechanical, etc.), the corresponding ion channels are activated, thus enabling the modulation of neuronal activity with higher levels of precision and local modulation. In this review, first, we focused on the relationship between biological nerve signals and stem cell differentiation, and tumor development. In addition, the effects of magnetic nanomaterials on biological neural signals and the tumor environment were discussed. Finally, we introduced the application of magnetic-nanomaterial-mediated electromagnetic stimulation in regenerative medicine and its potential in the field of cancer therapy.